STUDI TINGKAT KINERJA PEGAWAI DINAS PERPUSTAKAAN DAN ARSIP PROVINSI KALIMANTAN TENGAH - Devi Avita Sari; Slamet Winaryo; Piter Joko Nugroho (Equity In Education Journal, 2023)
This study aims to determine the level of performance of employees of the Central Kalimantan Province Library and Archives Service, seen from the dimensions: (1) Service Orientation, (2) Integrity, (3) Commitment, (4) Discipline, and (5) Cooperation. The type of research used is descriptive quantitative. The population in this study were employees at the Central Kalimantan Province Library and Archives Service, totaling 18 people with Echelon III and IV status, where all populations were samples (total sample). The data collection technique is a questionnaire / questionnaire. The results showed that in general the performance level of employees at the Central Kalimantan Province Library and Archives Service was in the "Fair enough" category. The results of this study answered and strengthened the phenomena that the researchers found in the initial study, where in reality the high or low results of employee performance appraisals based on PKP did not necessarily reflect the actual conditions in the field. Discipline of employees (librarians) is still a real problem that must be immediately addressed by the Central Kalimantan Province Library and Archives Service in an effort to improve the quality of service for users.